2012
DOI: 10.1186/1471-2474-13-41
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal symptoms and computer use among Finnish adolescents - pain intensity and inconvenience to everyday life: a cross-sectional study

Abstract: BackgroundMusculoskeletal symptoms among adolescents are related to the time spent using a computer, but little is known about the seriousness of the symptoms or how much they affect everyday life. The purpose of the present study was to examine the intensity of musculoskeletal pain and level of inconvenience to everyday life, in relation to time spent using a computer.MethodsIn a survey, 436 school children (12 to 13 and 15 to 16 years of age), answered a questionnaire on musculoskeletal and computer-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
3
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 28 publications
8
62
3
16
Order By: Relevance
“…Xavier et al 18 state that adolescents abusively using electronic devices have higher chances (OR=1.52) of having headache. The literature also states that overload of visual system and maintenance of inadequate postures for long periods are reflected in headache reports by adolescents 2,9 . Notwithstanding our results being in agreement with most current literature and presenting statistical and social relevance, the study was limited by the fact of generalizing results for students of a public school and extending them to private school students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xavier et al 18 state that adolescents abusively using electronic devices have higher chances (OR=1.52) of having headache. The literature also states that overload of visual system and maintenance of inadequate postures for long periods are reflected in headache reports by adolescents 2,9 . Notwithstanding our results being in agreement with most current literature and presenting statistical and social relevance, the study was limited by the fact of generalizing results for students of a public school and extending them to private school students.…”
Section: Discussionmentioning
confidence: 99%
“…Devices such as cell phones, computers, electronic games, tablets and TV have been used both for school purposes and leisure 2,3 . Due to easy access to electronic devices more time is spent with them and, as a consequence, negative impact on adolescents' health have been reported in the literature, such as sleep changes, tiredness, anxiety, depression, overweight, de-ORIGINAL ARTICLE DOI 10.5935/1806-0013.20150049 creased levels of physical activities, decreased concentration, musculoskeletal pain, stress and headache [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Sitting in a bad posture for more than two hours a day may leads to moderately-severe musculoskeletal syndrome. (Hakala, Saarni, & Pun, 2012). They studied MSS on adolescents and found that everyday lives of these young people are affected by this problem.…”
Section: International Journal Of Academic Research In Business and Smentioning
confidence: 99%
“…Some studies show a relation between a low level of physical activity and neck/shoulders pain (7,8,9), while others (10,11,12,13,14,15,16) do not report an association between physical activity and neck/ shoulders pain among school students.…”
Section: Introductionmentioning
confidence: 99%